Electromagnetic field in seedlings, yield and quality of corn in field conditions - Zepeda-Bautista, Rosalba; Virgen-Vargas, Juan; Suazo-López, Francisco; Domínguez-Pacheco, F. Arturo; Rodríguez-Rebollar, Hilda; Hernández-Aguilar, Claudia (Revista Mexicana de Ciencias Agrícolas, 2019)
To improve productivity and quality of corn grain (Zea mays L.) for human consumption, without damaging the environment, the effect of the electromagnetic field (EMF) on physiological quality, yield and health of corn grain was evaluated. The seed was exposed to EMF at an intensity of 3.6 mT. Under field conditions, in 2015 and 2016, varieties were evaluated: H-70, H-61R and V-60 and three times of exposure to EMF (6, 12 and 24 min) more a control (non-irradiated) in a design of random complete blocks. The results showed that the seed exposed for 24 min to EMF increased 10.54% and two days the establishment of seedlings and the average male flowering; likewise, 11.04% the yield ha-1 (870 kg ha-1) compared to the non-irradiated control. H-70 and V-60 had higher establishment of seedlings with 24 minutes of exposure to EMF (17.5 and 8.23%) and H-61R with 12 min (9.75%). H-61R and V-60 yielded more (10.85 and 8%) with 12 min of EMF exposure and H-70 increased 27.14% with 6 min compared to the control. The grain was quantified on average 9.22 and 7.72% of Fusarium spp. and Fusarium oxysporum. With 12 min of EMF exposure, the presence of Fusarium spp. in comparison with the control. Electromagnetic field, used as seed pre-sowing treatment of corn varieties, significantly increases the establishment of seedlings, but not the grain yield under field conditions.